African American Recruitment in Early Heart Failure Palliative Care Trials: Outcomes and Comparison With the ENABLE CHF-PC Randomized Trial. Issue 1 (January 2023) - Stockdill, Macy L.; Dionne-Odom, J. Nicholas; Wells, Rachel; Ejem, Deborah; Azuero, Andres; Keebler, Konda; Sockwell, Elizabeth; Tims, Sheri; Burgio, Kathryn L.; Engler, Sally; Durant, Raegan; Pamboukian, Salpy V.; et al.
Background: Palliative care trial recruitment of African Americans (AAs) is a formidable research challenge. Objectives: Examine AA clinical trial recruitment and enrollment in a palliative care randomized controlled trial (RCT) for heart failure (HF) patients and compare patient baseline characteristics to other HF palliative care RCTs. Methods: This is a descriptive analysis the ENABLE CHF-PC (Educate, Nurture, Advise, Before Life Ends: Comprehensive Heartcare for Patients and Caregivers) RCT using bivariate statistics to compare racial and patient characteristics and differences through recruitment stages. We then compared the baseline sample characteristics among three palliative HF trials. Results: Of 785 patients screened, 566 eligible patients with NYHA classification III-IV were approached; 461 were enrolled and 415 randomized (AA = 226). African Americans were more likely to consent than Caucasians (55%; P FDR = .001), were younger (62.7+ 8; P FDR = .03), had a lower ejection fraction (39.1+ 15.4; PFDR = .03), were more likely to be single ( P FDR = .001), and lack an advanced directive (16.4%; P FDR < .001). AAs reported higher goal setting (3.3+ 1.3; P FDR = .007), care coordination (2.8+ 1.3; P FDR = .001) and used more "denial" coping strategies (0.8+ 1; P FDR = .001). Compared to two recent HF RCTs, the ENABLE CHF-PC sample had a higher proportion of AAs and higher baseline KCCQ clinical summary scores. Conclusion: ENABLE CHF-PC has the highest reported recruitment rate and proportion of AAs in a palliative clinical trial to date. Community-based recruitment partnerships, recruiter training, ongoing communication with recruiters and clinician co-investigators, and recruiter racial concordance likely contributed to successful recruitment of AAs. These important insights provide guidance for design of future HF palliative RCTs. Trial Registration: ClinicalTrials.gov Identifier: NCT02505425